Маршал Жуков. Каким мы его помним: [сборник воспоминаний] / примечания Е. Н. Цветаева - Цветаев Е. Н. (Политиздат, 1989)
Экземпляры: аб. ЦБ (20211002) / Инвентарный номер: 11555 / Цена: / Сис.шифр: 63.3(2)622 / Авт.знак: М 30 / ББК: 63.3(2)622,88